2013
DOI: 10.21930/rcta.vol13_num2_art:259
|View full text |Cite
|
Sign up to set email alerts
|

Efecto sobre la producción de carne de la aplicación de tecnologías de renovación de praderas de Bothriochloa pertusa (L.) A. Camus en la Costa Norte Colombiana

Abstract: <p>Uno de los factores que limitan de manera importante la competitividad y sostenibilidad del sector ganadero de la región Caribe es la degradación de suelos y praderas. El objetivo del estudio fue evaluar en fincas del departamento del Atlántico y dedicadas a la de producción de carne, el efecto de las tecnologías de renovación de praderas como la intervención mecánica con labranza vertical, establecimiento de una nueva gramínea, aplicación de un plan de fertilización y pastoreo rotacional, sobre la pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…This behavior could be predicted, since the grasses stockpiled in August were used earlier, compared to the other months. As the grass plant matures, there is a reduction in cellular content and, consequently, a decline in CP levels (Magalhães et al, 2009;Cajas-Girón et al 2012, González et al, 2014Valbuena et al, 2016;Fontinele et al, 2022), as observed in this work. In general, in silvopastoral systems, pastures tend to have better nutritional value, showed higher CP contents than conventional pastures (Souza et al, 2007, Barragán-Hernández et al, 2019.…”
Section: Grassessupporting
confidence: 61%
“…This behavior could be predicted, since the grasses stockpiled in August were used earlier, compared to the other months. As the grass plant matures, there is a reduction in cellular content and, consequently, a decline in CP levels (Magalhães et al, 2009;Cajas-Girón et al 2012, González et al, 2014Valbuena et al, 2016;Fontinele et al, 2022), as observed in this work. In general, in silvopastoral systems, pastures tend to have better nutritional value, showed higher CP contents than conventional pastures (Souza et al, 2007, Barragán-Hernández et al, 2019.…”
Section: Grassessupporting
confidence: 61%
“…Pasture renovation includes practices such as mechanization, fertilization, weed control, planting grass and/or leguminous species, rotational grazing, and, depending on the degree of pasture degradation, the use of different combinations of the above. Therefore, it is clear that by implementing this type of technologies, it is possible to increase forage and beef production and farm income (Cajas-Girón et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Se conoce que aproximadamente el 90% del área establecida en pasto en el departamento del Atlántico se encuentra en algún nivel de degradación (Cajas-Girón et al, 2011). Uno de los factores responsables de esta situación es el mal manejo del pastoreo, práctica que depende del productor.…”
Section: Rotación De Potrerosunclassified